2020
DOI: 10.1111/edt.12621
|View full text |Cite
|
Sign up to set email alerts
|

Global status of knowledge for prevention and emergency management of traumatic dental injuries in dental professionals: Systematic review and meta‐analysis

Abstract: Background Dental professionals are the primary care providers for traumatic dental injuries (TDI). The dental traumatology literature has a number of studies evaluating the knowledge of dental professionals from different parts of the world but its global status is unknown. Hence, the aim of this systematic review was to assess the global status of knowledge for the prevention and emergency management of TDI in dental professionals and to provide recommendations for future research. Materials and Methods The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 59 publications
(631 reference statements)
2
35
0
1
Order By: Relevance
“…A recent survey among Lithuanian general dental practitioners showed that they lacked sufficient knowledge of dental trauma. 29 Researchers have also observed similar findings in other countries as demonstrated in the global study of dental professionals' knowledge by Tewari et al, 30 possibly because general dental practitioners may possess only moderate knowledge of TDI, whereas specialists in endodontics and pediatric dentistry possess greater knowledge, 31 medical doctors also often lack sufficient knowledge of dental trauma. 32 The most frequent complications were pulp necrosis, periapical periodontitis, and abscess formation, occurring in 94% of primary and 54% of permanent teeth.…”
Section: Discussionsupporting
confidence: 62%
“…A recent survey among Lithuanian general dental practitioners showed that they lacked sufficient knowledge of dental trauma. 29 Researchers have also observed similar findings in other countries as demonstrated in the global study of dental professionals' knowledge by Tewari et al, 30 possibly because general dental practitioners may possess only moderate knowledge of TDI, whereas specialists in endodontics and pediatric dentistry possess greater knowledge, 31 medical doctors also often lack sufficient knowledge of dental trauma. 32 The most frequent complications were pulp necrosis, periapical periodontitis, and abscess formation, occurring in 94% of primary and 54% of permanent teeth.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, no papers were found from regions and countries with developed oral health programmes, such as Scandinavia, Canada, or the United Kingdom. Systematic reviews of knowledge on TDIs by Tewari and co-authors also revealed discrepancies in the geographical distribution of studies [ 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevention and posttraumatic management methods should be widely known, but numerous studies have shown a low level of such knowledge in the general population as well as among teachers, sports coaches, and even among healthcare professionals, including dentists [ 4 , 6 , 7 , 8 , 9 , 10 , 11 ]. Therefore, effective and efficient information about dental trauma seems to be essential.…”
Section: Introductionmentioning
confidence: 99%
“…Getting a professional emergency managementat the site of accident is mandatory, that would decrease the time between avulsion and replantation,and Consequently decrease the risk of having internal and external root resorption (35,36) . 51% of GDPs chose the answer to splint avulsed teeth for 7 to 10 days , which was higher in comparison with other studies were only 10-30% had chosen this answer (15,22) . 136 (66.0%) of GDPs chose the answer that they would never do replantation for primary tooth, result was improved by the educational program to 182 (88.3%) which is consistent with (176) Nada A.…”
Section: For General Dental Practitionersmentioning
confidence: 68%
“…The time taken by the patients to go to the dentist from the site of the accident especially in case of avulsion, as well as proper storage media are mandatory for prognosis and survival of the avulsed tooth (15) . Incorrect handling and long time out of the oral cavity may cause deformation of periodontal ligament, root resorption and may lead to ankylosis and tooth loss (9) .…”
Section: Discussionmentioning
confidence: 99%